Developing Pilates Training Model for Decreasing The Body Fat Ratio Among Overweight Women (Department of Physical Education, Sport, Health and Recreation, 2019)
The study aims at generating a sufficient alternative training model for decreasing the body fat ratio among overweight women. The study refers to the research and development model by Borg & Gall. When the study was conducted, a total of 10 respondents were involved in small-scale test, a total of 17 respondents were involved in big-scale test and a total of 12 respondents were involved in product effectiveness test. Then, in order to be selected as the subject in the study the respondents should be overweight women who became the members of gymnastics studio in the Province of Yogyakarta Special Region. Then, the instrument in the study was attained from the expert judgment and the suggestions by Pilates instructors through questionnaire distribution and body fat ratio measurement. In analysing the data, the descriptive analytical technique was employed and the paired sample t-test was employed specifically on the product effectiveness test. The results of the study are in the form of Pilates training model that has been validated by 2 experts. The Pilates training model itself consists of 14 warming-up movements, 22 main movements and 11 cooling-down movements. Furthermore, the results of the study show that the developmet of Pilates training model for decreasing the body fat ratio has already been valid in terms of burning the body fat. In addition, the results of the test show that the development of Pilates training model has belonged to the â€œGoodâ€ category.